2021
DOI: 10.3389/fphys.2020.608347
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Intermittent Hypoxia and Left Ventricular Remodeling in Patients With Obstructive Sleep Apnea-Hypopnea Syndrome

Abstract: The present study was undertaken to examine the association between intermittent hypoxia and left ventricular (LV) remodeling and explore which parameter of intermittent hypoxia is most relevant to LV remodeling in patients with obstructive sleep apnea-hypopnea syndrome (OSAHS). Two hundred eighty six patients underwent polysomnographic examination were enrolled. Based on apnea-hypoxia index (AHI), patients were divided into no, mild, moderate and severe OSAHS groups. Between-group differences in LV remodeling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…Using PWD,Chan et al, (2009) also observed a higher right ventricular MPI in children with moderate to severe OSAS (confirmed by PSG) than in those with mild OSAS and those without OSAS. Consistent to prior reports;Deng et al, 2021 also showed that the values of IVS and LVIDs were higher in patients with severe OSAHS than those without OSAHS or those with less severe OSAHS. Furthermore, they also observed that the LVM and LVMI-height were also significantly higher in patients with severe OSAHS.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Using PWD,Chan et al, (2009) also observed a higher right ventricular MPI in children with moderate to severe OSAS (confirmed by PSG) than in those with mild OSAS and those without OSAS. Consistent to prior reports;Deng et al, 2021 also showed that the values of IVS and LVIDs were higher in patients with severe OSAHS than those without OSAHS or those with less severe OSAHS. Furthermore, they also observed that the LVM and LVMI-height were also significantly higher in patients with severe OSAHS.…”
supporting
confidence: 91%
“…These findings strongly indicate that presence of OSAHS is significantly associated with LV remodeling. Moreover,Deng et al, 2021 also found that severe OSAS patients had slight LVH.…”
mentioning
confidence: 92%
“…Our results indicate that free-fed ob/ob mice exposed to acute IH exhibit cardiac changes present with OSA, namely an increase in LV mass, interventricular septum thickness, and LV dilation (Yu et al, 2020;Deng et al, 2021). OSA increases one's risk for both concentric and eccentric cardiac hypertrophy (Cuspidi et al, 2020).…”
Section: Discussionmentioning
confidence: 73%
“…Deng et al 18 from China, concluded that male gender, high body mass index, systolic and diastolic blood pressure and use of antihypertensive drugs were associated with compromised left ventricular function. We generated similar results as our data also showed that comorbid Type-2 DM, Hypertension and high BMI had a statistically significant relationship with left ventricular systolic dysfunction among patients suffering from sleep apnea syndrome.…”
Section: Discussionmentioning
confidence: 99%